2013
DOI: 10.7567/jjap.52.05db19
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Pitch Copper Wiring Formed with Super-Inkjet and Oxygen Pump

Abstract: We have successfully printed wires of 5 µm line widths and spaces in copper nanoparticle ink with a super-inkjet printer. The wires show resistivity as low as 8.1 µΩ·cm after sintering at 250 °C in an extremely low oxygen atmosphere generated by an oxygen pump. To our knowledge, this is the first report of micron-scale copper wiring formed by a direct printing method without any masks or templates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…3 shows examples of suitable samples prepared under controlled humidity. Micro-patterning devices could also be used to place CG particles around biological targets 33 . Our method is compatible with droplets of samples ejected from a liquid jet injector 34 if CG is added to the sample solution.…”
Section: Discussionmentioning
confidence: 99%
“…3 shows examples of suitable samples prepared under controlled humidity. Micro-patterning devices could also be used to place CG particles around biological targets 33 . Our method is compatible with droplets of samples ejected from a liquid jet injector 34 if CG is added to the sample solution.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that repeated oxidization in air and reduction in low p(O 2 ) can produce printed copper wiring of fairly low resistivity [3]. Although the resistivity could become under 10 μΩ·cm, the grains hardly grew from the original nanoparticles (see Fig.…”
Section: N Shirakawamentioning
confidence: 99%
“…Although the resistivity could become under 10 μΩ·cm, the grains hardly grew from the original nanoparticles (see Fig. 6 in [3]). …”
Section: N Shirakawamentioning
confidence: 99%
“…If the viscosity of the ink is too high, the ink cannot be loaded to the tip of the nozzle. The metal nanoparticle conductive inks have been intensively printed high-density circuitry for a MEMS Device 80 , source/drain electrodes in OFETs 79 and other electronics applications, such as resistive fuse-type write-once-readmany (WORM) memory 78 , metallization of the through silicon vias 84 and mm-wave bandpass filter 82 . The low viscosity of the ink mentioned above was typically in the range of 5 20 mPa•s, and the resolution reached 2 μm.…”
Section: ∼ ∼mentioning
confidence: 99%